ΥΠΗΡΕΣΙΕΣ ΥΠΟΒΟΗΘΟΥΜΕΝΗΣ ΔΙΑΒΙΩΣΗΣ. - Διγώνης, Στέφανος (Perioperative Nursing)
Introduction: The assisted living systems (AAL) patients developed personalized, adaptive and prudential requirements, which require high quality of service in order to achieve interoperability, usability, security, and accuracy. Aim: Exploration of Ambient Assisted Living (AAL). Material & Method: Regarding of methodology, conducted a literature review (international & Greek) using scientific database PubMed & Google Scholar. Used only articles that were the criteria we set primarily like to refer to implementation of a clear program. Excluded publications reported empirical results. The chronological limitation from 2007 to today entered because the first of the European Commission in the joint program Independent living. Results: The results show that modern technologies have entered in the healthcare field with the aim of improving patients' quality of life. Assisted living play a crucial role in social inclusion and in providing equal access to health services for older people and people with disabilities. Development of the assisted living system for these people requires the acceptance of technology. The deterioration of the patient's health makes it difficult or even impossible to use an assisted living device in the long run, and it is therefore necessary to continuously evaluate usability of the devices and systems for each user. Conclusions: Technological maturity and increased health expenditures will lead to decentralization of healthcare from hospital to home.